Flow Intermittence Drives the Benthic Algal Composition, Biodiversity and Diatom-Based Quality of Small Hilly Streams in the Pannonian Ecoregion, Hungary - B-Béres, Viktória; Kókai, Zsuzsanna; Várbíró, Gábor; Mustazhapova, Gulperizat; Csabai, Zoltán; Pernecker, Bálint; Borics, Gábor; Bácsi, István; Boda, Pál (Frontiers in Ecology and Evolution, 2022)
Climate change is putting increasing pressure on flowing waters. Drastic water level fluctuations in rivers or drying up of small and medium-sized streams all contribute to the biodiversity crisis threatening freshwater ecosystems. Benthic diatoms are important elements of biofilm in small streams. However, knowledge on the relationship between benthic diatoms and flow intermittence is incomplete, especially in regions recently impacted by recurrent drying. Thus, we investigated benthic diatom flora of small intermittent, hilly streams in the warm temperate region of Europe (the Pannonian Ecoregion). Our hypotheses were addressed to compositional changes, biodiversity loss and diatom-based ecological assessment. The results revealed clear flow intermittence-induced differences in taxa and trait composition of diatoms. Altogether six species for the dry phase and three species in the aquatic phase were identified as indicative ones by using indicator value analyses. In contrast to water regime induced changes in assemblages, there was a seasonal overlap in taxa and trait composition. During the study period, the drying up of streams did not result in significant biodiversity loss either at taxa or trait levels. Functional dispersion, however, reduced significantly by summer. Overall, neither the hydrological regime nor seasonal changes had a significant effect on diatom-based quality indices, except for the Rott trophic index (TID index). The TID index values were significantly lower in dry phases than in aquatic ones. These results suggested that the drying up of streams has a very complex influence on benthic diatoms. It seems that taxonomical and functional redundancy can reduce the negative impact of short-time flow intermittence on assemblages. As a practical benefit, the results are the first to support the use of diatom-based quality indices in the assessment of flow intermittence in the temperate region.